Enabling desired disposal of compostable plastic packaging: an evaluation of disposal instruction labels - Allison, Ayşe Lisa; Băitanu, Alexandra; Purkiss, Danielle; Lorencatto, Fabiana; Michie, Susan; Miodownik, Mark (Frontiers in Sustainability, 2024)
This study evaluated a series of disposal instruction labels for their effectiveness in enabling the desired disposal of compostable plastic packaging. Mixed methods were employed: an online experiment and a survey. UK citizens (n =1,008) completed a task, sorting packaging labelled with various disposal instructions into one of three bins (general waste, food waste, recycling). They also selected a preferred compostable disposal instruction logo and provided reasons for their preference. Items lacking disposal instructions followed intuitive disposal practices; items with a common practice of being compostable were most frequently disposed of into food waste, items with a common practice of being recycled were most frequently disposed of into recycling and items with a common practice of being disposed of with general waste were most frequently disposed of with general waste. 'Do not recycle' was effective at diverting compostable plastic packaging to general waste. The label 'compost with food waste' had the highest rate of correct disposal in the food waste bin when compared to the control group and to the 'compost' disposal instruction. 'Compost with food waste', however, was not statistically different from 'put with food waste' or 'recycle with food waste'; all three led to statistically similar rates of disposal in the food waste bin. Findings suggest that citizens struggle to identify compostable plastic packaging from appearance alone. Clear direct disposal instruction wording can help enable the appropriate disposal behaviours. Qualitative findings showed that participants preferred clarity and directness in the disposal instructions logo denoting compostability. The depiction of simple yet unambiguous and instructive symbols was valued and likely to be the better instigators of behaviour change compared with associative symbols. Implications for labelling policy are discussed.